Predictions Models of Preventive Health Effort Coverage With Stunting Prevalence in Toddlers, Indonesia - Nuryanto, Nuryanto; Widowati, Evi; Pawenang, Eram Tunggul; Cahyati, Widya Hary (Journal of Creativity Student, 2025)
The achievement of stunting reduction in Indonesia is still below the national target. The low coverage of preventive health efforts in several regions is one of the causes of the high prevalence of stunting in Indonesia. The purpose of this study is to analyze the modeling of the coverage of preventive health efforts with the prevalence of stunting in toddlers in Indonesia. A type of analytical descriptive research with a cross-sectional design. The research data is sourced by Indonesian Health Profile, 2023. The collected data was then processed and analyzed using simple and multiple regression statistical tests. There was a linear relationship between coverage of complete basic immunization, monitoring the growth of childs, implementation of GERMAS, and proper sanitation with the prevalence of stunting in toddlers in Indonesia (p-value ≤ 0.05). The coverage of monitoring the growth of childs and proper sanitation was feasible to significantly predict the prevalence of stunting in toddlers in Indonesia (p-value ≤ 0.05) with the regression model equation being stunting = 55.837-0.211*CMGT-0.209*CPSA. The increasing coverage of monitoring the growth of childs and proper sanitation was predicted to further reduce the prevalence of stunting in childs in Indonesia. There is a need to improve the coverage of monitoring the growth of childs and proper sanitation, especially in low-coverage areas through an integrative and comprehensive approach that involves the active participation of the government, communities, and other sectors.